Studi Pengukuran Kemampulabaan Perusahaan Sektor Perdagangan, Jasa Dan Investasi - Marpaung, Bintang Sahala; Sukadi, Johanes (LPPM Institut Bisnis dan Informatika Kesatuan, 2016)
This study is aimed at gathering information on profitability in trading, service and investment companies. The variables investigated and related to companies’ profitability are consisted of: working capital variable (X1), cash turnover (X2), and inventory turnover (X3) acting as independent variable and return on asset (ROA) as dependent variable (Y). The population in this research is companies running in trading, service and investments and are listed in Indonesia Stock Exchange (BEI) during the period of 2010-2014. Samples collection method is using purposive sampling technique for as much as 15 companies. The data used are secondary ones. The calculation and data analysis revealed by classic assumption tests show that research data are normally distributed, and there is not any multicollinearity issue, heteroscedasticity and autocorrelation problems are not occurred. Data test results show that working capital, cash turnover, and inventory turnover have positive impacts on return on assets (ROA). This is proven with the following regression equation : Y = 4,58 – 0,11 X1 + 0,01 X2 + 0,01 X3.